Playing and Learning in the Creative Corner: Efforts to Increase Early Childhood Creativity Through the Introduction of Letters and Numbers at Nurul Muslimin Kindergarten - Anggraini, Elya Siska; Ginting, Khairunnisa Ababil Br.; Sihombing, Enjelina Vincere; Manalu, Ines (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research aims to overcome challenges in increasing the creativity of young children at Nurul Muslimin Kindergarten, especially in recognizing letters and numbers. The research background emerged from an understanding of the limitations of learning media and the lack of teacher creativity which influenced children's understanding in kindergarten. The research subjects involved 15 children and 1 teacher in the class, using qualitative research methods through direct observation and documentation of each learning session. The research results showed that there were positive changes in the understanding of letters and numbers for young children after implementing learning media in the creative corner. Children showed an increase in their active participation and interest in learning, and looked more enthusiastic in various play activities in the creative corner. Positive interactions between teachers and children also increase, creating a more dynamic learning atmosphere. The conclusion of this research is that the play while learning approach in the creative corner has a positive impact on young children's understanding of letters and numbers. The implication is that the application of learning media that supports a creative approach can increase the effectiveness of learning in kindergarten, providing a positive impact on the development of creativity in early childhood.